ナンキョクイキ デノ カイエン リュウシ タイキチュウ ノ ヘンシツ カテイ ト カイヒョウ セキセツ チュウ ノ ソセイ ブンベツ カテイ - 原, 圭一郎; ハラ, ケイイチロウ; 長田, 和雄; オサダ, カズオ; 林, 政彦; ハヤシ, マサヒコ; 矢吹, 正教; ヤブキ, マサノリ; 橋田, 元; ハシダ, ゲン; 山内, 恭; ヤマノウチ, タカシ; et al. (2010)
P(論文) 昭和基地(1997-1998,2003-2006; JARE-38-39,JARE-44-47)とドームふじ基地(1997,JARE-38)で,エアロゾル成分と酸性ガスの連続観測を実施した.海塩粒子濃度の季節変化はいずれの基地でも夏季に極小を示し,冬季に濃度が高くなる変化を示した.冬季に海塩粒子濃度が高いのは,低気圧接近に伴う強風による海塩粒子の発生と長距離輸送に起因しているのだろう.昭和基地では,海塩粒子のほとんどが微小粒子域(D_p: 0.2-2.0 μm),超微小粒子域(D_p<0.2 μm)に分布していた.海塩粒子中のCl^- とBr^- は不均一反応により損失しやすく,夏季にCl^- とBr^- の損失が顕著だった.昭和基地で観測されたCl^- Na^+ とBrv Na^+ の各濃度比は,夏季にはそれぞれ約0.5,0まで減少していた.昭和基地では,冬季に海塩粒子はほとんど変質(Cl^- ロス)していなかったが,ドームふじ基地では年間を通じて海塩粒子からのCl^- 損失が確認された.冬季のドームふじ基地では,NO_3^- とその前駆物質により海塩粒子の変質が進行していた.昭和基地でのガス状の無機塩素化合物(主成分はHCl)と臭素化合物(主成分はHBr)の濃度は,それぞれ0.2-9.4 nmol m^<-3>,検出下限以下～ 1.5 nmol m^<-3> だった.海塩組成分別によるSO_4^<2-> 損失は昭和基地だけでなく,内陸のドームふじ基地でも確認された.Mg^<2+> Na^+ の濃度比の季節変化は,低温下で濃度比が高くなる傾向を示した.濃度比の値とその温度依存性から,Mirabilite形成以外の海塩組成分別過程(例えばGypsum,Hydrohaliteの形成)も南極沿岸域で起きていることが示唆される.ドームふじ基地と昭和基地でのMg^<2+> Na^+ 比の季節変化や値が大きく異なっていたことから,内陸部でも積雪表面で海塩組成分別が進行し,風により大気中へ海塩粒子が再飛散している可能性が考えられる. Observations of aerosol constituents and acidic gases were carried out at Syowa Station (1997-1998 and 2003-2006; JARE-38～ 39, and JARE-44～ 47) and Dome Fuji Station (1997, JARE-38). Seasonal variations and size distribution of sea-salt particles were compared between coastal and inland stations. Seasonal variations of the concentrations of sea-salt particles showed a minimum in the austral summer and higher during the winter at both stations due to strong winds and long-range transport. Sea-salt particles were mostly distributed in fine (D_p: 0.2-2.0 μm) and ultra-fine (D_p<0.2 μm) modes at Syowa Station. Particulate Cl^- and Br^- are liberated preferentially from sea-salt particles through the heterogeneous reactions at Syowa and Dome Fuji Stations in the summer. The molar ratio of Cl^- Na^+ and Br^- Na^+ at Syowa Station decreased to ca. 0.5 and ～0, respectively, in summer. Fewer sea-salt particles were modified at Syowa Station during the winter, whereas sea-salt particles were modified through the year at Dome Fuji Station. In particular, sea-salt particles were modified with NO_3^- and its precursors ...